2017
DOI: 10.1038/jp.2016.229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nasal continuous positive airway pressure on the pharyngeal swallow in neonates

Abstract: Oral feeding while on-nCPAP significantly increases the risk of laryngeal penetration and tracheal aspiration events. We recommend caution when initiating oral feedings on nCPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…A recent study showed that preterm infants under nCPAP have the same ability to initiate pharyngeal reflexive swallowing as their room-air-breathing counterparts and concluded that preterms can protect and clear a pharyngeal bolus with appropriate proximal peristaltic mechanism (12). Conversely, results from a recent videoscopic study in preterm infants suggest that nCPAP alters pharyngeal swallows and increases the risk of tracheal aspiration during oral feeding (20). Overall, our present results showing better oxygenation in nCPAP lambs during bottle-feeding, together with the absence of deleterious cardiac events, is reassuring.…”
Section: Safety Of Bottle-feeding Under Ncpapmentioning
confidence: 99%
“…A recent study showed that preterm infants under nCPAP have the same ability to initiate pharyngeal reflexive swallowing as their room-air-breathing counterparts and concluded that preterms can protect and clear a pharyngeal bolus with appropriate proximal peristaltic mechanism (12). Conversely, results from a recent videoscopic study in preterm infants suggest that nCPAP alters pharyngeal swallows and increases the risk of tracheal aspiration during oral feeding (20). Overall, our present results showing better oxygenation in nCPAP lambs during bottle-feeding, together with the absence of deleterious cardiac events, is reassuring.…”
Section: Safety Of Bottle-feeding Under Ncpapmentioning
confidence: 99%
“…Until now, the variable results and conflicting conclusions of the available clinical studies ( 7 12 ) have precluded the publication of evidence-based guidelines for feeding infants under NRS. Consequently, initiation of oral feeding in preterm infants under NRS remains a controversial topic among neonatologists ( 9 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the risk of tracheal aspiration in fragile preterm infants fed orally under nCPAP ( 11 ), we initiated a research program in newborn ovine models a few years ago with the aim of gaining new physiological knowledge on the effect of NRS on the precise coordination between sucking, swallowing, and breathing as well as on bottle-feeding efficiency and safety. We believe that observations in ovine models will ultimately help in designing safer clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of pharyngeal pressure generated by this airflow on airway protection is also of concern, as studies have indicated varying level of pressure generated based on patient size and cannula diameter/ nasal occlusion. [73][74][75][76] Some studies suggest the possibility of oral feeding with HFNC, [77][78][79][80][81] and with CPAP, 82,83 while others raise concerns for increased aspiration with nasal CPAP, 84,85 and BiPAP. 86 Without definitive guidance from large studies, the ICU clinician must consider each patient's individual presentation and risk factors, not solely the oxygen delivery mode/level in isolation of these other factors.…”
Section: Timingmentioning
confidence: 99%